Karakter Islami dalam Perspektif Filsafat Pendidikan di MI Slubung Blitar - Efendi, Mohamad Yusuf; Basiran, Basiran (Jurnal Dirosah Islamiyah, 2024)
This research aims to determine the Islamic character at MI Slubung Blitar and Islamic character from the perspective of educational philosophy at MI Slubung Blitar. So this research raises the title "Islamic Character in the Perspective of Educational Philosophy at MI Slubung Blitar". This type of research is descriptive qualitative field research. The data collection method uses interview and documentation data collection techniques. Interviews were conducted with fiqh teachers and aqidah akhlaq teachers. Documentation was carried out to obtain document information related to research on Islamic character from the perspective of educational philosophy. The results of the research show that the Islamic character formed at MI Slubung Blitar is the 5 S (Smile, Greetings, Greetings, Politeness and Politeness), lining up, reading students' promises and shaking hands, reading prayers together before starting to study, carrying out Duha prayers and prayers. dhuhur in congregation, carrying out Muraja'ah, and carrying out the rituals of Hajj. Judging from the philosophy of education, the Islamic character formed at MI Slubung Blitar is in line with the philosophy of Realism. In the context of Realism, character education is the process of habituating learners or students to creating a climate (creating an atmosphere) of goodness (virtue).